(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fGTQ GdGee hefTQ GdQbe hHYO aEfg deG cGfJ UfGYI GdWH ef CaVd GdUfGYGJ hCQHM GdJLGQGJ s
(3BNQgG (B:s
(3hdceGd GdOhdI ef GdcJH cJGH cTa GdeTcdGJ hGjVGM GdeaUdGJ ai JaSjQ GdbQGf Je GdHGH GdYGTQ ef cJGH Yjhf GdGfHGA ai WHbGJ GdGWHGA s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B47 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B96s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1185s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(8148) s
Keywords: (3GdJGQjNs